Tsenguluso ya zwiila zwa matshilisano kha Tshivenda - Pandelani, Konanani Joyce (My University, 2011)
The mini-dissertation shows that language and culture go hand in hand. For instance, in Tshivenḓa taboos are largely reflected through language. This study highlights social taboos that exist in Tshivenḓa and how they impact on Tshivenḓa as a language. If someone does not understand the language that is used to express taboos, he or she is likely to violate these taboos. The study deals with social taboos pertaining to marriage, death, birth, relations between relatives and strangers and so on. Nowadays these taboos are becoming unfamiliar and as such this negatively impacts on the use of Tshivenḓa as well as relations among people.
Thesis (M. A. (Tshivenda)) --University of Limpopo, 2011
Keywords: Taboos; Tshivenda language; Taboo, linguistics; Taboo -- South Africa -- Limpopo; Venda language